Plasma Tissue Factor Pathway Inhibitor (TFPI) Levels in Healthy Subjects and Patients with Hemophilia A and B - Gu, Jian-Ming; Patel, Chandra; Kauser, Katalin (Blood, 2015)
BAY 1093884 is a fully human monoclonal antibody against tissue factor pathway inhibitor (TFPI) developed as a potential bypass agent for patients with hemophilia with or without inhibitors. It restores insufficient thrombin burst, leading to stable clot formation in hemophilic conditions in vitro, and effectively stops bleeding in vivo. TFPI is a potent inhibitor of factor Xa (FXa) and the factor VIIa tissue factor complex in the extrinsic pathway. The majority of TFPI is associated with vascular endothelial cells. The mean plasma TFPI concentration in healthy individuals is ~70 ng/mL (1.6 nM) and about 80% of the circulating TFPI is bound to lipoproteins [Dahm, et al. Blood. 2003;101(11):4387-4392; Broze,et al. Front Biosci. 2012;17:262-280]. Some reports indicate that patients with hemophilia B have lower free TFPI levels than patients with hemophilia A, irrespective of phenotypic severity (Tardy-Poncet, et al. Haemophilia 2011;17:312-313). The objective of this study is to determine the plasma TFPI concentration in healthy donors and patients with hemophilia by a newly developed functional TFPI capture assay and to evaluate this assay with inhibition of TFPI by anti-TFPI neutralizing antibody (BAY 1093884) in vitro. A quantitative enzyme-linked immunosorbent assay using FXa as capture agent was developed and validated to measure TFPI levels in human plasma. The assay shows very good precision, accuracy, and reproducibility and should capture all coagulation-relevant forms of TFPI from plasma. Plasma TFPI was determined in 30 healthy donors (15 males and 15 females) and 30 patients with severe hemophilia (hemophilia A [n=12], hemophilia A with inhibitors [n=9], hemophilia B [n=9]). The plasma TFPI levels (mean ± SD) in healthy individuals, patients with severe hemophilia A without and with inhibitors, and severe hemophilia B were 59.5±18.4 ng/mL, 62.9±14.6 ng/mL, 47.3±4.3 ng/mL, and 68.1±8.8 ng/mL, respectively (Table 1). No statistical differences were found based on sex or race (Hispanic, African American, white) in the healthy population and between patients with hemophilia with and without inhibitors. TFPI levels were also not affected by addition of corn trypsin inhibitor (CTI) in citrate plasma. Furthermore, the concentration that inhibits 50% of TFPI levels (IC50) of anti-TFPI antibody (BAY 1093884) was determined to be 4.76 nM in normal human plasma using this assay. In conclusion,plasma TFPI does not appear to be affected by sex or race in healthy subjects, or the deficiency of factor VIII or IX in patients with hemophilia. The functional TFPI capture assay could potentially be used as a pharmacodynamic marker for monitoring plasma TFPI levels after the administration of anti-TFPI antibody and guide dosing strategies. Table 1Plasma TFPI Levels in Healthy Subjects and Patients With Severe Hemophilia A and BHealthyHuman Donors(n=30)SevereHem A(n=12)Severe Hem AWith inhibitors(n=9)SevereHem B(n=9)TFPI, ng/mL Mean ± SD59.5±18.462.9±14.647.3±4.368.1±8.8Hem=hemophilia; TFPI=tissue factor pathway inhibitor. Gu:Bayer HealthCare: Employment. Patel:Bayer HealthCare: Employment. Kauser:Bayer HealthCare LLC: Employment.